INNOVATION AND GOVERNANCE IN SHIPPING: THE SAFETY NAVIGATION INFORMATION SYSTEM (SIKAPAL) MODEL AND SAFETY MITIGATION SYSTEM IN SUMENEP REGENCY - Hidayat, Imam; Magfirli, Arief Khoir; Shafira, Shoumi; Iyas, Moh Kholilurrahman; Rasaili, Wilda (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
Sumenep Regency has 126 islands within its territory, divided into 19 sub-districts on the mainland and 8 sub-districts in the marine or island areas. In the past five years, the rate of maritime accidents in Sumenep Regency has been relatively high, with a history of shipwreck incidents. The government needs to offer appropriate solutions to address these naval accidents. An innovation from the government concerning the issues in Sumenep Regency is creating the SiKaPal program (Maritime Safety System) as a tangible form of the government’s concern for Sumenep Regency. This study aims to understand the maritime safety mitigation system and explain the SiKaPal model as an innovation in the governance of marine safety. This research uses a descriptive qualitative method with data collection and analysis conducted through primary data obtained from interviews with key ship informants regarding the implementation of security management operations that have been carried out so far, including the obstacles encountered in the implementation of SiKaPal. The Sumenep Regency government, through the Communication and Information Agency (Diskominfo), initiated SiKaPal (Maritime Safety System) to address the occupational safety issues of fishermen in Sumenep Regency. Maritime safety innovation has become a solution and an answer to the existing problems. SiKaPal (Maritime Safety System) is the only innovation that uses AIS (Automatic Identification System) and is available only in Sumenep Regency. Governance innovation can enhance the capacity of public sector innovation because it is often seen as an alternative rather than a complement. The integration of the SiKaPal system and safety mitigation measures serves as an innovation model for more effective ship safety management.